Brain atrophy in natalizumab-treated patients with multiple sclerosis: a 5-year retrospective study - Eisele, Philipp; Szabo, Kristina; Ebert, Anne; Platten, Michael; Gass, Achim (Journal of neuroimaging, 2019)
BACKGROUND AND PURPOSE Studies demonstrated a higher brain volume loss in the first year after initiation of natalizumab treatment than in the second year, but the experiences beyond 24 months are scarce until now. We investigated the evolution of brain volume changes in multiple sclerosis (MS) patients receiving natalizumab for at least 60 months. METHODS Using annual 3-dimensional magnetization-prepared rapid acquisition gradient-echo (MPRAGE) sequences acquired on a 3 Tesla magnetic resonance imaging (MRI), we investigated percentage brain volume changes (PBVCs) in 10 MS patients (9 women, mean age at baseline MRI = 29 ± 9 years; median Expanded Disability Status Scale = 2 ± 1.5; mean disease duration = 6 ± 5 years) after 12, 24, 36, 48, and 60 months. RESULTS PBVCs were statistically higher during the first 12 months (−1.48 ± 1.05%) when compared to 12-24 months (−.6 ± .61%; P < .05), but not between 12-24 and 24-36 months (−.43 ± .54%), 24-36 and 36-48 months (−.28 ± .49%), and 36-48 and 48-60 months (−.33 ± .49%; P > .05 for all comparisons). CONCLUSION Our results contribute to the increasing knowledge of PBVCs in natalizumab-treated MS patients. Our data suggests that after a significant PBVC decrease in the first year, brain atrophy rates show a slowdown during long-term follow-up.